Relocalisation de sources anciennes, textuelles et matérielles du XXe siècle : les « aires culturelles » de la vigne en Bourgogne en question - Guillaume Grillon; Jean-Pierre Garcia (Bulletin du Centre d’Études Médiévales d’Auxerre)
This communication shows, from the André Lagrange’s archives, the relocation of the tools of the vineyard before the arrival of phylloxera. André Lagrange is an associate ethnologist at the “Musée des Arts et Traditions Populaires de Paris” (Paris Museum of Arts and People Traditions). These archives are kept at the “Archives Municipales de Beaune” (Beaune Municipal Archives). First, we shall speak about methodology. The archives are from the XXth century but they are similar to the ancient sources that the historians of the Middle Age or of the modern era deal with, taking in account that the data are not complete and that the wine growers witnesses of the practical experiences or users of those tools have died. So incomplete are the data of the ethnologist who has built that documental research up. With that relocation, some information collected on the field are discussed: the scale of representation of the distribution of the tools of the pre-phylloxera vineyard, the spheres of cultural influence built from André Lagrange’s maps with their technical, social or naturalist interpretation, the relevance of those spheres of influence as tools of cultural and historical reflection in ethnology, in archaeology and in linguistics.